An evaluation of health risks of nano building products used for IAQ management in smart environment - Bilgin, Sezgin; Tuna Taygun, G.; Müjdem Vural, Sadiye (IOS Press, 2022)
Smart technologies create controlled and sustainable systems to meet rapid urbanisation and various needs arising from this urbanisation throughout the world. Some of these systems are realised with nano-technology. Especially in the construction industry, nano products are used in smart building and smart material applications. Some of the products developed with this technology are also used to control indoor air. However, it is seen that nano-sized materials produced artificially with nano-technology have possible health risks on the environment and human health due to various unknowns. In addition, nanomaterials in the content of nanoproducts, can enter the human body through respiration, ingestion and skin contact due to their very small size. This chapter examined the possible effects of nanomaterials in sensors and healing nanoproducts produced to control indoor air quality on user health. The role of nano-smart materials in sustainable building design was evaluated. With the data obtained in this context, it aims to reveal the positive and negative situations caused by the use of nanoproducts to benefit from their improved properties and allow users to make choices considering this information. © 2022 The authors and IOS Press.
Keywords: Human and environmental health; Indoor air quality; Nano-technology; Nanomaterial; Smart material